2016
DOI: 10.7150/ijbs.16529
|View full text |Cite
|
Sign up to set email alerts
|

MiR-99a and MiR-491 Regulate Cisplatin Resistance in Human Gastric Cancer Cells by Targeting CAPNS1

Abstract: Cisplatin is the first-line agent utilized for the clinical treatment of a wide variety of solid tumors including gastric cancer. However, the intrinsic or acquired cisplatin resistance is often occurred in patients with gastric cancer and resulted in failure of cisplatin therapy. In order to investigate if miRNA involves in cisplatin resistance of human gastric cancer, we first screened and compared the expression of miRNAs between cisplatin resistant gastric cancer cell lines SGC-7901/DDP and BGC-823/DDP and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 42 publications
5
43
2
1
Order By: Relevance
“…We for the first time observe upregulation of miR-99a, miR-145 and downregulation of miR-18b in PAC-resistant cell line. Upregulation of miR-99a was observed in CIS-resistant gastric cancer cell lines [73] and vincristine-resistant acute lymphoblastic leukemia (ALL) [74]. In contrast to our study, downregulation of miR-145 was observed in PAC-resistant variants of A2780 and SKOV-3 ovarian cancer cell lines [75].…”
Section: Discussioncontrasting
confidence: 99%
“…We for the first time observe upregulation of miR-99a, miR-145 and downregulation of miR-18b in PAC-resistant cell line. Upregulation of miR-99a was observed in CIS-resistant gastric cancer cell lines [73] and vincristine-resistant acute lymphoblastic leukemia (ALL) [74]. In contrast to our study, downregulation of miR-145 was observed in PAC-resistant variants of A2780 and SKOV-3 ovarian cancer cell lines [75].…”
Section: Discussioncontrasting
confidence: 99%
“…Deregulation of specific miRs, associated with tumor development and progression, has been observed in gastric cancer along with drug resistance (7,8). Therefore, investigating the roles of these miRs may help improve the diagnosis and treatment of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In a current study, miRNA‐132 was verified to promote cisplatin resistance in a GC stem cell‐like Lgr5 cells both in vitro and in vivo, which used to be mediated through the regulation of SIRT1/CREB/ABCG2 signaling pathway . The sensitivity of GC cells to cisplatin can enhance by a low expression level of miR‐99a and miR‐491 through targeting CAPNS1/calpain1/calpain2/caspase‐3/PARP1 signaling pathway directly …”
Section: Mirnas and Drug Resistance In Gcmentioning
confidence: 72%
“…172 The sensitivity of GC cells to cisplatin can enhance by a low expression level of miR-99a and miR-491 through targeting CAPNS1/calpain1/calpain2/ caspase-3/PARP1 signaling pathway directly. 174…”
Section: Role Of Mirnas In Signaling Pathways Of Gcmentioning
confidence: 99%